sj-docx-1-eso-10.1177_23969873221135915 – Supplemental material for Comparative analysis of core and perfusion lesion volumes between commercially available computed tomography perfusion software ... - Suomalainen, Olli P; Martinez-Majander, Nicolas; Sibolt, Gerli; Bäcklund, Katariina; Järveläinen, Juha; Korvenoja, Antti; Tiainen, Marjaana; Forss, Nina; Curtze, Sami (SAGE Journals, 2022)
Supplemental material, sj-docx-1-eso-10.1177_23969873221135915 for Comparative analysis of core and perfusion lesion volumes between commercially available computed tomography perfusion software by Olli P Suomalainen, Nicolas Martinez-Majander, Gerli Sibolt, Katariina Bäcklund, Juha Järveläinen, Antti Korvenoja, Marjaana Tiainen, Nina Forss and Sami Curtze in European Stroke Journal ...